Annual report of the Cocoa Research Institute of Nigeria: 1966-67 - Cocoa Research Institute of Nigeria ([Ibadan] Cocoa Research Institute, 1966)
Annual report of the Cocoa Research Institute of Nigeria for 1966-67. The report further highlights some of the administrative functions of the cocoa research institute including staff position and promotion guidelines.
rpm 31/01/2019
Loans
Keywords: Cocoa; Nigeria